Music and death funeral music, memory and re-evaluating life - Marx, Wolfgang 1967-; Edwards, Peter (Boydell Press, 2023)
Music gives specific meanings to our lives, but also to how we experience death; it forms a central part of death rituals, consoles survivors, and celebrates the deceased.